Testis-specific peroxiredoxin 4 variant is not absolutely required for spermatogenesis and fertility in mice - Homma, Takujiro (Sci Rep, 2020)
PRDX4, a member of peroxiredoxin family, is largely concentrated in the endoplasmic reticulum (ER) and plays a pivotal role in the redox relay during oxidative protein folding as well as in peroxidase reactions. A testis-specific PRDX4 variant transcript (PRDX4t) lacks the conventional exon 1, which encodes the signal peptide that is required for entry into the ER lumen, but instead carries alternative exon 1, which is transcribed from the upstream promoter in a testis-specific manner and results in the PRDX4t protein being localized in the cytosol. However, the potential roles of PRDX4t in male genital action remain unknown. Using a CRISPR/Cas9 system, we first disrupted the testis-specific promoter/exon 1 and generated mice that were specifically deficient in PRDX4t. The resulting PRDX4t knockout (KO) mice underwent normal spermatogenesis and showed no overt abnormalities in the testis. Mating PRDX4t KO male mice with wild-type (WT) female mice produced normal numbers of offspring, indicating that a PRDX4t deficiency alone had no effect on fertility in the male mice. We then generated mice lacking both PRDX4 and PRDX4t by disrupting exon 2, which is communal to these variants. The resulting double knockout (DKO) mice were again fertile, and mature sperm isolated from the epididymis of DKO mice exhibited a normal fertilizing ability in vitro. In the meantime, the protein levels of glutathione peroxidase 4 (GPX4), which plays an essential role in the disulfide bond formation during spermatogenesis, were significantly increased in the testis and caput epididymis of the DKO mice compared with the WT mice. Based on these results, we conclude that the disruption of the function of PRDX4t in the spermatogenic process appears to be compensated by other factors including GPX4.